2024
DOI: 10.3390/ijerph21020234
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Emergency Department Users with Psychiatric Disorders Related to Barriers to Outpatient Care

Tiffany Chen,
Zhirong Cao,
Francine Ferland
et al.

Abstract: Emergency department (ED) overcrowding is a growing problem worldwide. High ED users have been historically targeted to reduce ED overcrowding and associated high costs. Patients with psychiatric disorders, including substance-related disorders (SRDs), are among the largest contributors to high ED use. Since EDs are meant for urgent cases, they are not an appropriate setting for treating recurrent patients or replacing outpatient care. Identifying ED user profiles in terms of perceived barriers to care, servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Though several quantitative studies have assessed determinants of unmet needs for care among patients with MD [7,8], few have examined these unmet needs in relation to high ED use [6,9]. Some qualitative studies that explored high ED use among patients with MD found that unmet care needs partly explained high ED use [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though several quantitative studies have assessed determinants of unmet needs for care among patients with MD [7,8], few have examined these unmet needs in relation to high ED use [6,9]. Some qualitative studies that explored high ED use among patients with MD found that unmet care needs partly explained high ED use [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Another mixed methods study found the following needs to be most associated with high ED use: needing to talk to someone, to get medication, to nd relief from psychiatric symptoms or to be hospitalized [5]. A recent study found three pro les of ED users with MD, one of which included high ED users with the greatest barriers to care; these patients also reported the lowest service satisfaction and the poorest perceived mental/physical health conditions [9]. Other qualitative investigations reported a combination of structural and motivational care barriers that justi ed high ED use, with structural barriers being most prevalent [12].…”
Section: Introductionmentioning
confidence: 99%